Migratory Fish Bone in the Thyroid Gland: Case Report and Literature Review - EnHao Wu; Lei Huang; Ya Zhou; Xun Zhu (Case Reports in Medicine)
Introduction. Foreign body stuck in the throat is a common emergency case, which can be removed by the endoscopic treatment. Fish bones are one of the common observed foreign bodies in the pharynx or cervical esophagus. Fish bones have a risk of damaging the mucosa when lodged in the upper digestive tract. Foreign bodies of fish bones located outside the laryngopharyngeal tissue are relatively unusual, and it is even more rare that they remain in the thyroid. It may cause local infection, abscess formation, large blood vessels rupture, and other serious life-threatening complications when the position of the fish bone migrates to the neck. We present a unique case of a 31-year-old woman in whom a fish bone was found in the thyroid. The fish bone had been removed successfully two months after the onset of symptoms. The relevant literature is reviewed and summarized. Case Presentation. A foreign body which is located in the neck area by swallowing is usually found in the emergency case. One of the commonest foreign bodies is the fish bone. The common presenting symptoms include foreign body (FB) sensation and or a sharp pain during swallowing. But we report a rare case in which a migratory fish bone stuck in the thyroid gland was found after 3 months. We retrieved previous literature and made a summary. Conclusions. Fish bones are not easy to be found as a foreign body. Surgeons should be aware that fish bones can become lodged in the thyroid gland. Combined with the history should be a wary fish bone to migrate to the case of the thyroid, to avoid misdiagnosis. To confirm the diagnosis, we can take ultrasound, computerized tomographic scanning (CT), and other tests.